Green microalgae cultured in textile wastewater for biomass generation and biodetoxification of heavy metals and chromogenic substances. (September 2019) - Oyebamiji, Olufunke O.; Boeing, Wiebke J.; Holguin, F. Omar; Ilori, Olusoji; Amund, Olukayode
Abstract: Wastewater treatment is expensive and algae are increasingly tested for their usefulness in cleaning wastewater. Here, we evaluated six microalgae isolates for their ability to grow in textile wastewater. The sequences of the genes coding for the 18S, ITS 1 and ITS 2 regions placed all algae isolates in the Chlorellaceae family (green algae). Biomass was generated for each algae strain with textile wastewater diluted with deionized water and algal dry weight of 0.4–1.35 g L −1 was obtained. Elemental analyses of the wastewaters were carried out before and after cultivation of the algae strains and dye colour removal was also estimated. Supernatant obtained after biomass harvest showed reduction/removal of heavy metals like Al, Cu, V, Pb and Se. Chromogenic substances present in the textile wastewater were also reduced by 47.10–70.03% at a lambda max of 558 nm. Highlights: The wastewater generated microalgal biomass ranging from 0.4 to 1.35 g L −1 . The microalgae removed heavy metals like Pb, Al, V, Cu and Se. Chromogenic substances were also reduced by 47.10–70.03%.